The Effect of Different Solvents and Methods on Brown Seaweed Turbinaria sp. Metabolite Profil - Handayani, Ervina; Frediansyah, Andri; Prasedya, Eka Sunarwidhi; Sunarwidhi, Anggit Listyacahyani (Jurnal Biologi Tropis, 2024)
Turbinaria sp. is valuable source of various metabolites that exhibit pharmacological and biological activities. The diversity of these metabolites can be influenced by several factors, such as environmental conditions and the choice of solvent during the extraction process. This study aims to investigate the effect of different solvents and methods on the metabolite profiles of Turbinaria sp. extract Turbinaria sp. was extracted using maceration and soxhlet method with n-hexane and n-hexane:methanol as solvents. Phytochemical analysis was performed using tube tests. Meanwhile the determination of total phenols and total flavonoids was performed by spectrophotometry assay. The results has shown that Turbinaria sp. contain flavonoids, alkaloids, terpenoids, phenols, and tannins, with the highest total phenol and total flavonoid content found in the extracts using n-hexane as a solvent and soxhletation methods.